2020
DOI: 10.1002/bkcs.11980
|View full text |Cite
|
Sign up to set email alerts
|

Protein Adsorption and Bacterial Adhesion Resistance of Cross‐linked Copolymer Hydrogels Based on Poly(2‐methacryloyloxyethyl phosphorylcholine) and Poly(2‐hydroxyethyl methacrylate)

Abstract: Herein, the preparation of the cross-linked copolymer hydrogels composed of various weight ratios of 2-methacryloyloxyethyl phosphorylcholine (MPC) and 2-hydroxyethyl methacrylate (HEMA) monomers employing free-radical polymerization was reported. The integration of the MPC monomer into HEMAbased hydrogels showed good transmittance (>90%) and enhanced the water content retention (79-202%) relative to those of pure HEMA-based hydrogel. Notably, the MPC-containing hydrogels (MPC-H) exhibited the improved anti-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…It was because of the high hydrophilic properties from the enriched hydrophilic shell of MPC, which had been caused by zwitterionic, representing bacteria's unfavorable binding on the hydrophilic surface. This study also confirmed the unfavorable adhesion of bacteria on the hydrophilic surface 97 . However, some hydrophobic polymers can cause membrane disruption and bacterial destruction.…”
Section: Impact Of Wettability and Extracellular Polymeric Substancessupporting
confidence: 78%
See 1 more Smart Citation
“…It was because of the high hydrophilic properties from the enriched hydrophilic shell of MPC, which had been caused by zwitterionic, representing bacteria's unfavorable binding on the hydrophilic surface. This study also confirmed the unfavorable adhesion of bacteria on the hydrophilic surface 97 . However, some hydrophobic polymers can cause membrane disruption and bacterial destruction.…”
Section: Impact Of Wettability and Extracellular Polymeric Substancessupporting
confidence: 78%
“…This study also confirmed the unfavorable adhesion of bacteria on the hydrophilic surface. 97 However, some hydrophobic polymers can cause membrane disruption and bacterial destruction. The interaction of hydrophobic hydrogel and bacteria has been described by Irwansyah I.…”
Section: Impact Of Wettability and Extracellular Polymeric Substancesmentioning
confidence: 99%
“…However, single pHEMA-based hydrogels have little commercial application; thus, numerous studies have been conducted to modify pHEMA structure with the aim of improving its properties, for example, using cross-linking agents such as ethylene glycol dimethacrylate (EGDMA) [ 41 ] and tetra(ethylene glycol) diacrylate (TEGDA) [ 42 , 43 ] to enhance its mechanical properties, or β-cyclodextrin-hyaluronan (β-CDcrHA) to reduce tear protein absorption in a contact lens [ 129 ]. Another approach is to copolymerize pHEMA with other polymers, commonly with polyacrylamide (PAA) [ 130 ] or ethylene glycol dimethacrylate (EGDMA) [ 40 ] to improve its mechanical properties, poly (ethylene glycole) diacrylate (PEGDA) to improve host biosensors or enhance its water absorption capacity [ 131 ], glycidyl methacrylate (GMA) [ 132 ] to facilitate cell attachment and proliferation, or 2-methacryloyloxyethyl phosphorylcholine (MPC) [ 133 ] to improve the water content retention and anti-biofouling properties. Moreover, other possibilities to improve pHEMA-based hydrogels’ performance for biomedical applications include the formation of composites, e.g., pHEMA with boric acid (BA), with interesting applications as soft contact lens material, as reported by Ulu et al (2018) [ 134 ], or the formation of IPNs with gelatin to enhance biological properties for in vitro and in vivo performance [ 135 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the anti-protein adsorption capability of zwitterionic poly(carboxybetaineacrylamide)s with several carbon atoms between the cation and anion weakens when the carbon atom count exceeds two, as its hydrophilicity diminishes [59] . Additionally, the hydrophilicity of CO 2and PO 4is significantly greater than that of SO 3 - [60] . Consequently, the anti-fouling ranking is poly[carboxybetaine methacrylate (CBMA)] > poly[2-methacryloyloxyethyl phosphorylcholine (MPC)] > polySBMA.…”
Section: The Non-fouling Performancementioning
confidence: 93%